ANALYSIS OF RISK FACTORS OF DIABETIC FOOT ULCER IN DIABETES MELLITUS PATIENTS - Vina Vitniawati; Sri Mulyati Rahayu; Irisanna Tambunan (Universitas Muhammadiyah Kudus, 2023)
Diabetes Mellitus (DM) is a chronic metabolic disorder caused by the pancreas not using insulin effectively, if the management is not good, one of the risks of complications in DM patients is Diabetic Foot Ulcer. Behaviors at risk for causing Diabetic Foot Ulcer are smoking activities, physical activity, use of poor footwear, body mask index and glycemic control. The behavior of DM patients greatly influences the incidence of Diabetic Foot Ulcer, therefore it is very important to analyze the behavioral factors of DM patients who are at risk for Diabetic Foot Ulcer. The aim of this research is to analyze the behavioral factors that are at risk for the occurrence of Diabetic Foot Ulcer and to look for the most dominant factors that are at risk of causing Diabetic Foot Ulcer. The research was conducted using a descriptive method on 30 respondents using a total sampling technique. The data collection process used questionnaires about smoking activities, physical activity, use of poor footwear, body mask index and glycemic control. The results obtained for risk behaviors for Diabetic foot ulcers were 70% normal BMI, 93.7% had non-smoking habits, 50% did physical activity, 66.67% used footwear, 66.67% went on a diet and 100% did glycemic control . The behavior of DM patients who are at risk of developing Diabetic Foot Ulcer are all indicators only if sorted from the most dominant, namely Physical Activity, Diet and Use of Footwear, BMI, Smoking Habits and Glycemic Control. Suggestions for the pronalis program to provide education that emphasizes behavior that is at risk of developing diabetic foot ulcers. Key Word : Behavioral, Diabetes Mellitus, Diabetic Foot Ulcer,